2020
DOI: 10.1371/journal.pone.0241465
|View full text |Cite
|
Sign up to set email alerts
|

What triggers online help-seeking retransmission during the COVID-19 period? Empirical evidence from Chinese social media

Abstract: The past nine months witnessed COVID-19's fast-spreading at the global level. Limited by medical resources shortage and uneven facilities distribution, online help-seeking becomes an essential approach to cope with public health emergencies for many ordinaries. This study explores the driving forces behind the retransmission of online help-seeking posts. We built an analytical framework that emphasized content characteristics, including information completeness, proximity, support seeking type, disease severit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 86 publications
4
48
1
Order By: Relevance
“…Next, our temporal analyses pointed to a steady decline in people's expressed psychosocial concerns during the 2-month study period (Figures 1 and 2), which conforms with similar findings in Google search queries as stay-at-home orders and other COVID-19-related policy changes were implemented in the United States [105]. We note contemporary social computing research studying various aspects of the social media discourse related to COVID-19 [63,[106][107][108]. By providing complementary evidence to observations by Mackey et al [106] and Stokes et al [107] on expressed (mental health) concerns during the crisis, our study further underscores their findings using a comparable (control) data set, reinforcing and providing empirical credibility to the impression that the COVID-19 pandemic has indeed caused or contributed directly to the mental health concerns that we describe.…”
Section: Comparison With Prior Worksupporting
confidence: 82%
See 1 more Smart Citation
“…Next, our temporal analyses pointed to a steady decline in people's expressed psychosocial concerns during the 2-month study period (Figures 1 and 2), which conforms with similar findings in Google search queries as stay-at-home orders and other COVID-19-related policy changes were implemented in the United States [105]. We note contemporary social computing research studying various aspects of the social media discourse related to COVID-19 [63,[106][107][108]. By providing complementary evidence to observations by Mackey et al [106] and Stokes et al [107] on expressed (mental health) concerns during the crisis, our study further underscores their findings using a comparable (control) data set, reinforcing and providing empirical credibility to the impression that the COVID-19 pandemic has indeed caused or contributed directly to the mental health concerns that we describe.…”
Section: Comparison With Prior Worksupporting
confidence: 82%
“…Oh et al [62] further showed that surveyed Facebook users demonstrated a positive relationship between having health concerns and seeking health-related social support. Indeed, during global crises such as COVID-19, when many of the physical sites for health care (including mental health) have been closed or have restricted access, it is likely that online support has proliferated [63]. Fear of potential infection may further have alienated individuals in need to pursue formal treatment, therapy, and support, perhaps channelizing their support-seeking efforts online and on social media.…”
Section: Support Expressionsmentioning
confidence: 99%
“…In addition to these biological aspects, the pandemic may also trigger emotional and behavioral coping, including psychological distress, fear of the COVID-19, and help-seeking behaviors (Ornell et al, 2020 ; Shigemura et al, 2020 ; Wang, Pan, Wan, Tan, Xu, Ho et al, 2020 ). Help-seeking behaviors, referring to reading articles related to psychological self-help, watching or listening to psychological online training video or audio, dialing psychological assistance hotline, etc., is a generally advocated behavioral strategy to cope with difficulties during public health emergencies (Luo et al, 2020 ). Research has found that all these COVID-19 related individual factors affected people’s life, indicating that less COVID-19 fear and psychological distress (Satici et al, 2020 ) and more help-seeking behaviors (Barros et al, 2020 ) were associated with better lives.…”
Section: A Holistic-interactionistic Perspectivementioning
confidence: 99%
“…In the meantime, people are prone to discuss health-related issues in this virtual sphere, especially during a public health crisis [ 13 ]. For example, during the COVID-19 era, some people disclosed their disease status on the internet for help-seeking [ 14 ], and a more substantial number of people talked about their own and others' symptoms as a mere natural reaction to the threat of illness [ 15 ]. Given those features, various internet platforms serve as fertile grounds for examining the public’s perceptions of health issues or events [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…China was one of the first countries severely affected by COVID-19. After implementing a series of strict prevention and control measures, the Chinese government tamed the virus in a comparatively short period; the so-called “China’s model to combat the COVID-19” set an example for other countries to combat this global health crisis [ 14 ]. Furthermore, China has taken great strides in developing COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%